The tenant of Wildfell Hall - Bronte, Anne, 1820-1849 (Penguin classics, 1996)
The mysterious new tenant of Wildfell Hall is a strong-minded woman who keeps her own counsel. Helen 'Graham' - exiled with her child to the desolate moorland mansion, adopting an assumed name and earning her living as a painter - has returned to Wildfell Hall in flight from a disastrous marriage. Narrated by her neighbour Gilbert Markham, and in the pages of her own diary, the novel portrays Helen's eloquent struggle for independence at a time when the law and society defined a married woman as her husband's property.